Probing nuclear effects in neutrino-nucleus scattering at the T2K off-axis near detector using transverse kinematic imbalances - Dolan, S (2017)
The precise characterisation of neutrino oscillations offers a range of auspicious opportunities in the search for physics beyond the standard model. In particular T2K and NOvA, as the current generation of accelerator-based long-baseline neutrino oscillation experiments, are just beginning to provide the first measurements of the complex phase that gives rise to CP-violation in the neutrino sector within the PMNS description of neutrino oscillations. However, the limiting systematic uncertainty in making such precision measurements of neutrino oscillations - and soon, for some measurements, the largest of all uncertainties - stems from a naivety of relevant O(GeV) neutrino-nucleus interactions. These interactions are particularly difficult to understand since the bare neutrino-nucleon scatter is often obfuscated by a variety of poorly-understood `nuclear effects', such as nucleon-nucleon correlations and hadronic re-interactions, which distort the outgoing particle kinematics. A better understanding of these nuclear effects is therefore essential to constrain the principle systematics associated with neutrino oscillation measurements. This thesis details how the T2K experiment's off-axis near detector is used to provide a novel characterisation of nuclear effects. This is achieved through the first measurement of differential neutrino-nucleus scattering cross sections as a function of kinematic imbalances in the plane transverse to an incoming neutrino beam. The use of transverse kinematic imbalances are motivated by a series of recent phenomenological studies, which this thesis further develops, that illustrate how these observables can provide a new examination of nuclear effects at T2K. In order to extract the cross sections with minimal input model bias, a new cross-section extraction procedure, which minimises the use of the input model and facilitates a data-driven regularisation, is developed, validated and applied. Extensive comparison of the results to the predictions of a variety of neutrino-nucleus interaction simulations then enables a unique probe, and partial isolation, of some nuclear effects. This probe is expected to play a significant role in future neutrino-nucleus interaction model development, whilst also facilitating new constraints on the principle systematic uncertainties associated with neutrino oscillation measurements.